2012
DOI: 10.1007/s12070-012-0579-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Validity of High Serum Antistreptolysin O Titre Only, as an Indication for Tonsillectomy

Abstract: Serum Antistreptolysin O (ASO) titre is raised when there is infection of any organ of the body, by Group A beta haemolytic streptococci (GABHS), Group C or Group G streptococci [1]. Increased serum ASO titre should not be the only deciding criterion for tonsillectomy if GABHS is not present in the palatine tonsils. In this study, we evaluate the rationality of performing tonsillectomy in raised serum ASO titre only, in absence of GABHS in palatine tonsil. The study was designed as a prospective cohort study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
2
6
0
2
Order By: Relevance
“…In comparison between the first group with high ASO titr and negative throat swab (104) and the second group with high ASO titre and positive swab (52), the improved rate was 27.4% in the first group and 84.4% in the second group with a p value of 0.001 which is statistically significant. Our results are in line with Hombrom et al 2012 [1] who concluded that one should perform throat swab culture along with ASO titre before doing tonsillectomy in absence of any other indications. Viswanathan et al 2000 [2], reported that there were significant reduction of sore throat attacks after tonsillectomy within one year after operation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison between the first group with high ASO titr and negative throat swab (104) and the second group with high ASO titre and positive swab (52), the improved rate was 27.4% in the first group and 84.4% in the second group with a p value of 0.001 which is statistically significant. Our results are in line with Hombrom et al 2012 [1] who concluded that one should perform throat swab culture along with ASO titre before doing tonsillectomy in absence of any other indications. Viswanathan et al 2000 [2], reported that there were significant reduction of sore throat attacks after tonsillectomy within one year after operation.…”
Section: Discussionsupporting
confidence: 92%
“…A single titre of more than 200 iu/ml is considered as a raised value. Serum ASO titre is raised when there is an infection of any organ of the body by GABHS, so the increased serum ASO titre should not be the only deciding criterion for tonsillectomy if GABHS is not present in the palatine tonsils [1]. GABHS is the most common bacteria that cause acute tonsillitis.…”
Section: Introductionmentioning
confidence: 99%
“…23 ASO titre remains the most sensitive serological indices of antecedent Group A beta-haemolytic streptococcal infection. 24 In present study it was observed that there was a reduction in ASO titres to levels <200 IU/ml post tonsillectomy. At the end of first follow up (1 month after surgery) 12 (48%) out of 25 patients showed ASO titre < 200 IU/ml; two tailed p-value = 0.0001, which was statistically significant.…”
Section: Discussionsupporting
confidence: 50%
“…в 13% случаев, что совпадает с данными других исследований [12]. Многие авторы отмечают низкую выявляемость Streptococcus pyogenes в мазках из глотки [6,12] и отдают предпочтение бактериологическому исследованию материала, полученного посредством тонкоигольной биопсии небных миндалин [13]. Повышение титра АСЛО зарегистрировано нами гораздо чаще, чем выявление БГСА, -у 42 (77,7%) из 54 больных.…”
Section: результаты и обсуждениеunclassified
“…[13] провели проспективное когортное исследование 50 больных с хроническим тонзиллитом, подвергнутых двусторонней тонзиллэктомии. Всем больным перед операцией проведено определение титра АСЛО и бактериологическое исследование материала, полученного с поверхности небных миндалин и при их тонкоигольной биопсии, которую многиe авторы считают «золотым стандартом» выявления БГСА [6,13]. При сравнении результатов трех исследований авторы пришли к заключению, что специфичность теста АСЛО при хроническом тонзиллите не превышает 12%.…”
Section: результаты и обсуждениеunclassified